Temperaturas y tiempos de pasteurización del guarapo sobre las características microbiológicas, fisicoquímicas y organolépticas para una bebida refrescante - Bermeo Pin, Marcos Leandro (2022)
One of the most common ways to consume sugar cane is in natural juice, considered a refreshing drink, in addition, it has a wide variety of uses. The present investigation aimed to evaluate the effects of time and temperature on the physicochemical, microbiological and sensory properties of guarapo to obtain a refreshing drink. A DCA (Completely Random Design) was applied in a factorial arrangement of 2 factors with 4 repetitions. In the execution phase, 16 experimental units were used, which were analyzed in the physicochemical (density, acidity, pH and ° brix), in the microbiological (molds and yeasts, total coliforms and fecal coliforms); A sensory test was performed on the best treatments by applying a hedonic scale where 1 is the lowest and 5 the highest with a Friedman test. All of the above specified will be executed in 4 treatments T1 90 ° Cx10min., T2 90 ° Cx 15min., T3 95 ° Cx10min., T4 95 ° C15min. It was possible to show that T1 and T2 were within the microbiologically permitted ranges. On the other hand, with respect to the physicochemical parameters, it only had an impact on acidity. Regarding the sensory evaluation, it was found that T2 (90 ° C x 15min) had greater acceptability.